Coppicing of two native but invasive oak species in Florida - Britez, Dario D.; Romero, Claudia; Putz, Francis E. (Forest ecology and management, 2020)
•Half the cut Quercus hemisphaerica and Q. nigra stems (5–19 cm DBH) survived 9 years.•Sprouting of 0 m, 1 m, and 1 m and split stems did not differ.•Root collar sprout survival was highest, sprouts from 1 m tall stumps was lowest.•Stumps suffered only modest wood decay.•Results affirm the benefits of herbicide treatments to reduce stump sprouting. Attempts to restore savannas are often thwarted by the resprouting of unwanted woody plants after they are top-killed by fire or mechanical treatments. In an effort to reduce stump sprouting of native to the region but invasive Quercus hemisphaerica (laurel oak) and Q. nigra (water oak) in an area being restored to longleaf pine (Pinus palustris) savanna, we treated 5–19 cm diameter stumps in ways opposite to the recommended practices for coppice management. Specifically, we created high stumps (1 m) and split half longitudinally (1 m-split); we also cut a sample at ground level (0 m), as recommended for coppice management. Over the 9-year observation period about 45% of the stumps died, with no treatment or species effects. Survival of individual sprouts was higher for Q. nigra than Q. hemisphaerica. In both species, sprouts from the 1 m stumps suffered the highest mortality rates, followed by the 0 m and 1 m-split treatments; number of sprouts per stump followed the same pattern (1 m > 0 m > 1 m-split). Root collar sprouts were more likely to survive than those that emerged higher on the stump or from rhizomes, and sprout mortality decreased with stump diameter in Q. nigra but not Q. hemisphaerica. Sprout survival decreased but sprout growth increased with canopy openness. About 40% of all sprouts were from rhizomes. Contrary to our expectation, wood decay was rare in all sprouts, regardless of their diameter or the height from which they emerged. These results confirm the benefits of treating stumps with herbicides to reduce unwanted trees in savannas undergoing restoration.